Ocena bioklimatycznych warunków rekreacji i turystyki w strefie polskiego Wybrzeża Bałtyku na podstawie wskaźnika UTCI = Assessment of bioclimatic conditions for recreation and tourism in the Polish Baltic coastal zone using the UTCI index - Koźmiński, Czesław. Autor; Michalska, Bożena. Autor (IGiPZ PAN, 2019)
The quality of a given bioclimate is much affected by the atmospheric environment (taken to include solar radiation, air temperature and humidity, atmospheric pressure, wind speed and levels of atmospheric pollution), as well as by geographical factors relating to topography and cover, the drainage system and land use (Owczarek 2009, Czarnecka, Nidzgorska-Lencewicz 2010, Koźmiński, Michalska 2011, Owczarek 2012). Tourists staying in a coastal area must contend with considerable variability of weather from one day to another, or even hour by hour, in the cold half-year in particular. Changes of weather have a profound effect on the human organism, inter alia giving rise to migraines, sleep disturbances and hypersensitivity. The work described here sought to assess temporal (inter alia seasonal) and spatial variability to heat loading of the human organism characterising the Polish Baltic coastal zone, as well as the temperature of water by beaches. It was to achieve this kind of assessments of bioclimate and its impact on the human organism that the index known as the UTCI (Universal Thermal Climate Index) was devised, taking in air temperature, wind speed, air humidity and absorbed solar radiation (expressed as mean radiant temperature) (Błażejczyk & Kunert, 2011). This index represents objective changes in physiological parameters of the human organism occurring thanks to differing environmental conditions as determined in relation to a 10-point scale for heat loading of the human organism (°C) that translate into descriptive terms ranging from extreme heat stress to extreme cold stress. UTCI values referred to here were calculated using BioKlima 2.6 software - http://www.igipz.pan.pl/Bioklima-zgik.html. Six zones for the heat loading of the human organism found to be present along the Polish coast during the four seasons of the year were designated by summing the frequency of occurrence of days with a particularly stimulating effect, be this severe or very severe heat stress or severe, very severe or extreme cold stress. The UTCI-based analysis sustained conclusions as follows: - The Polish Baltic coast is found to be characterised by marked day-to-day variability in the heat loading of the human organism, particularly in the November-late May period, with the result being a significant “nuisance” represented for tourists. - Along the western part of the coast and in the area of the Bay of Puck, conditions thermoneutral for the human organism were found to dominate (accounting for more than 60% of the days in a month) over the whole period from May through to mid-October. In the case of the northern part of the coast from Darłowo to Łeba the same was found to be true of the period extending from June through to the middle ten-day period of September, creating conditions favourable for outdoor recreation. - The duration of the bathing season with mean monthly water temperatures ≥18°C is of approximately 45 days along the coast from Darłowo to Łeba, 46-50 days in the central part of the coast, 46-60 days in the area of the Bay of Gdańsk and 61-70 in the area of the Bay of Pomerania. In most years under analysis, there was no identification of a bathing season with mean monthly water temperature ≥18°C in the Kołobrzeg and Władysławowo areas. - The bioclimatic conditions most favourable for recreation and tourism were identified for the area of the Bay of Pomerania, followed by the Bay of Gdańsk. Less-favourable conditions characterise the central part of the coast, while the least favourable circumstances extend through the northern area from Darłowo to Łeba, in which the bioclimate’s stimulatory effect is strongest.- The high spatial variability characterising heat loading of the human organism that it proved possible to identify for the Polish coast offers the possibility of particular regions and seasons being selected for recreation, in relation to tourists’ health status and specific requirements.
24 cm
Keywords: recreation; heat load; zones; bathing season; Baltic coast